Impact of postoperative complications on long‐term survival after esophagectomy in older adults: A SEER‐Medicare analysis. Issue 5 (5th July 2021) - Sesti, Joanna; Almaz, Biruk; Bell, Jaimie; Nguyen, Andrew; Bamboat, Zubin; Lackey, Adam; Langan, Russell C.; Turner, Amber L.; Hilden, Patrick; Paul, Subroto
Abstract: Background: Esophagectomy is a complex procedure associated with a high rate of postoperative complications. It is not clear whether postoperative complications effect long‐term survival. Most studies report the results from single institutions. Methods: We examined the Surveillance, Epidemiology and End Results (SEER)‐Medicare database to assess whether long‐term overall and cancer‐specific mortality of patients undergoing esophagectomy for cancer is impacted by postoperative complications. Results: Nine hundred and forty patients underwent esophagectomy from 2007 to 2014, of which 50 died, resulting in a cohort of 890 patients. Majority were males ( n = 764, 85.8%) with adenocarcinoma of the lower esophagus. Almost 60% of the group had no neoadjuvant therapy. Four hundred and fifty‐five patients had no major complications (51.1%), while 285 (32.0%) and 150 (16.9%) patients had one, two, or more major complications, respectively. Overall survival at 90 days was 93.1%. Multivariate analysis of patients followed up for a minimum of 90 days demonstrated that the number of complications was significantly associated with decreased overall survival but no impact on cancer‐specific survival. Conclusions: Our population‐based analysis with its inherent limitations suggests that patients undergoing esophagectomy who experience complications have worse overall survival but not cancer‐specific survival if they survive at least 90 days from the date of surgery. Highlights: Esophagectomy is a complex procedure associated with a high rate of complications. Whether postoperative complications effect long‐term cancer‐specific survival is unclear. This study using the SEER‐Medicare database found that patients who have complications after esophagectomy have worse overall survival but not cancer‐specific survival if they survive at least 90 days from the date of surgery.